The The Effect Of Person-Job Fit And Person-Organization Fit On Employee Performance With Individual Capacity As Moderation - Cindy Yonuari; Deni Septiawan; Anes Marcheline (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
This research was conducted due to a decline in the quality of Indonesia's human resources caused by various factors including poverty and unemployment levels. The quality of human resources in a country is assessed using GTCI or Global Talent Competitiveness Index published by INSEAD every year. Indonesia experienced a significant decline from the measurements carried out by GTCI in the Southeast Asia region. In 2020, Indonesia ranked 65th out of 132nd other countries, while in 2022 it decreased to 82nd out of 133rd countries. Indonesia also ranked as the 6th poorest country in Southeast Asia in 2023. To respond this issue, this study aims to enhance employee performance focused on private sector employees in the Jabodetabek area.. The population in this research were private employees who worked in the Jabodetabek area and the number of samples was determined using the Hair (2011) method with a total of 150 people. The sampling technique in this research is the convenience method with purposive sampling. This method is a sampling technique based on selecting respondents who are readily available or accessible to the researcher while still considering their relevance to the research objectives. This method is employed due to constraints in time and resources, prompting researchers to choose respondents who can be easily contacted or who possess characteristics that align with the research criteria. The study was carried out using questionnaires and a Likert scale ranging from 1 to 5. Statistical testing of the research data was assisted by Smart PLS software. The study evaluates person-job fit, person-organization fit, individual capacity, and their impact on employee performance. Data analysis was carried out using multiple regression techniques to test the relationship between the independent variables (person-job fit and person-organization fit), the moderator variable (individual capacity), and the dependent variable (employee performance). The results of this research are that if there is an increase or decrease in PJ fit, PO fit and individual capacity it will influence employee performance, while individual capacity cannot moderate PJ-fit and PO-fit in influencing employee performance. These findings underscore the importance for companies to prioritize enhancing person-job fit, person-organization fit, and individual capacity to foster improved employee performance, thereby addressing the broader challenge of enhancing Indonesia's human resource quality and competitiveness on the global stage.